2001
DOI: 10.1002/oa.584
|View full text |Cite
|
Sign up to set email alerts
|

Do environmental disturbances of an individual's growth and development influence the later bone involution processes? A study of two mediaeval populations

Abstract: Age-dependent cortical bone loss was studied in two mediaeval Polish populations differing with regard to socio-economic status, as well as the intensity of the occurrence of skeletal indicators of living conditions in the early stages of ontogenesis (compression of the skull base and the narrowing of the lumbar vertebral canal). Cortical bone loss was analysed on the basis of the radiographs of the second metacarpal. Cedynia population (better living conditions) is characterized by higher arithmetic means for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…More recently, Gosman and Ketcham () examined ontogenetic patterns in trabecular bone in the tibia in skeletons from the prehistoric Ohio Valley, noting changes in trabecular architecture from growth to skeletal maturity and with increasing ambulatory activities. A unique study by Rewekant () correlated growth patterns and developmental stress with variation in skeletal morphology and bone loss. Rewekant () examined the correlation of adult cortical bone loss with indicators of growth disturbance (specifically compression of the skull base and vertebral stenosis) in two Polish medieval populations with differing socioeconomic statuses.…”
Section: Bone Strength Maintenance and Loss Over The Life Coursementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Gosman and Ketcham () examined ontogenetic patterns in trabecular bone in the tibia in skeletons from the prehistoric Ohio Valley, noting changes in trabecular architecture from growth to skeletal maturity and with increasing ambulatory activities. A unique study by Rewekant () correlated growth patterns and developmental stress with variation in skeletal morphology and bone loss. Rewekant () examined the correlation of adult cortical bone loss with indicators of growth disturbance (specifically compression of the skull base and vertebral stenosis) in two Polish medieval populations with differing socioeconomic statuses.…”
Section: Bone Strength Maintenance and Loss Over The Life Coursementioning
confidence: 99%
“…A unique study by Rewekant () correlated growth patterns and developmental stress with variation in skeletal morphology and bone loss. Rewekant () examined the correlation of adult cortical bone loss with indicators of growth disturbance (specifically compression of the skull base and vertebral stenosis) in two Polish medieval populations with differing socioeconomic statuses. Greater metacarpal cortical bone loss was found in the population that also showed greater disturbance of bone growth during childhood (Rewekant, ).…”
Section: Bone Strength Maintenance and Loss Over The Life Coursementioning
confidence: 99%
“…Finally, experiences during growth and development are known to have a tremendous effect on adult bone maintenance and loss, and this has been demonstrated in both clinical (Cooper et al ., ; Javaid and Cooper, ; Javaid et al ., ) and bioarchaeological studies (Kneissel et al ., ; Boldsen, ; Mays, ; Rewekant, ; McEwan et al ., ; Gosman and Ketcham, ; Agarwal and Beauchesne, ). Osteoporosis is also not solely a direct product of menopause, there are many factors that contribute to advanced bone loss or help prevent it (Prentice, ; Schmitt et al ., ).…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…Research has shown that metacarpal cortical thickness is highly correlated with loss of bone mass at distant skeletal sites and particularly those with a predilection to fragility fracture (for example the distal radius, 4th lumbar vertebra, hip) (Haara et al, 2006;Ives and Brickley, 2005). Metacarpal cortical thickness can therefore be used to monitor and predict overall bone health and age-related bone loss (Mays, 2006(Mays, , 2001(Mays, , 2000(Mays, , 1996Rewekant, 2001). Radiogrammetry is a preferred method in bioarchaeological studies as it is non-destructive, and a relatively simple and inexpensive means of observation.…”
Section: Introductionmentioning
confidence: 99%
“…Bioarchaeologists have conducted numerous studies using metacarpal cortical bone radiogrammetry to investigate functional adaptation, growth, ageing, bone loss associated with osteoporosis and as a reliable indicator of fracture risk (Belkin et al, 1998;Himes et al, 1975;Ives and Brickley, 2005;Lazenby, 2002cLazenby, , 1998Lazenby, , 1995Mays, 2006Mays, , 2001Mays, , 2000Mays, , 1996Plato et al, 1982Plato et al, , 1984Rewekant, 2001). However, there have been very few works in the bioarchaeological literature on cortical bone loss in prehistoric skeletal materials making our investigation of cortical bone loss and fracture patterns in archaeological skeletons excavated from the Neolithic Community of Çatalhöyük, Turkey a unique addition to this body of work.…”
Section: Introductionmentioning
confidence: 99%